2020
DOI: 10.1186/s12913-020-05135-3
|View full text |Cite
|
Sign up to set email alerts
|

Training needs for Ugandan primary care health workers in management of respiratory diseases: a cross sectional survey

Abstract: Background: Respiratory diseases are among the leading causes of morbidity and mortality in Uganda, but there is little attention and capacity for management of chronic respiratory diseases in the health programmes. This survey assessed gaps in knowledge and skills among healthcare workers in managing respiratory illnesses. Methods: A cross sectional study was conducted among primary care health workers, specialist physicians and healthcare planners to assess gaps in knowledge and skills and, training needs in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…HCWs do not have su cient knowledge about asthma in children and as such, they are not able to assess the children presenting with respiratory symptoms appropriately. This is further supported by the ndings from a survey on primary care health workers' competencies that indicated that most of them were not comfortable to assess patients with chronic respiratory symptoms [14]. This study involved 3 medical doctors, 3 clinical o cers and 3 nurses.…”
Section: Clinical Characteristics Of the Childrenmentioning
confidence: 92%
See 1 more Smart Citation
“…HCWs do not have su cient knowledge about asthma in children and as such, they are not able to assess the children presenting with respiratory symptoms appropriately. This is further supported by the ndings from a survey on primary care health workers' competencies that indicated that most of them were not comfortable to assess patients with chronic respiratory symptoms [14]. This study involved 3 medical doctors, 3 clinical o cers and 3 nurses.…”
Section: Clinical Characteristics Of the Childrenmentioning
confidence: 92%
“…However, underdiagnosis of asthma in young children is still a big problem worldwide and the reasons are not very clear. It could be related to low awareness and understanding of the disease among caregivers and health care professionals, sub-optimal clinical assessment of the children with respiratory symptoms [13][14][15] and over-diagnosis of pneumonia according to the guidelines on Integrated Management of Childhood Illnesses (IMCI) [16]. In Uganda, a study in a tertiary care hospital indicated that over 90% of children with asthma symptoms were primarily diagnosed with pneumonia and treated with antibiotics [5].…”
mentioning
confidence: 99%
“…For example, the average startup cost per new hospital construction, human resources, medicines, and medical equipment is estimated at UGX.31.3 billion [ 26 ]. Despite the efforts of the government to prioritize primary healthcare, newly created districts occur in a context of related and continuing challenges of shortages of the health workforce at all levels, particularly frontline workers to screen and manage NCDs [ 28 , 29 ]. Effective coordination and provision of quality health services in newly created districts are likely to benefit from the availability and use of reliable data on key service needs to inform appropriate decision-making.…”
Section: Introductionmentioning
confidence: 99%